2022
DOI: 10.1038/s41467-022-28724-8
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection alters vaginal microbiome through down-regulating host mucosal innate peptides used by Lactobacilli as amino acid sources

Abstract: Despite the high prevalence of both cervico-vaginal human papillomavirus (HPV) infection and bacterial vaginosis (BV) worldwide, their causal relationship remains unclear. While BV has been presumed to be a risk factor for HPV acquisition and related carcinogenesis for a long time, here, supported by both a large retrospective follow-up study (n = 6,085) and extensive in vivo data using the K14-HPV16 transgenic mouse model, we report a novel blueprint in which the opposite association also exists. Mechanistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 90 publications
3
55
0
Order By: Relevance
“…Previous studies have shown that the incidence of BV 25,26 in women aged 20-45 years ranged from 29.2% to 38.5%, and the HR-HPV infection rate 27 in China was as high as 18.9%. Women with BV may also have a higher risk of HR-HPV infection.…”
Section: Prospective Follow-up Analysis Of 920 Participants Identifie...mentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that the incidence of BV 25,26 in women aged 20-45 years ranged from 29.2% to 38.5%, and the HR-HPV infection rate 27 in China was as high as 18.9%. Women with BV may also have a higher risk of HR-HPV infection.…”
Section: Prospective Follow-up Analysis Of 920 Participants Identifie...mentioning
confidence: 98%
“…Women with BV may also have a higher risk of HR-HPV infection. 10,12,25 However, the relationship between persistent infection of different genotypes of HR-HPV and BV remains unclear. To address this major issue, a 2-year prospective cohort study was performed including 920 women aged 20-45 years with different BV statuses (BV positive and BV negative).…”
Section: Prospective Follow-up Analysis Of 920 Participants Identifie...mentioning
confidence: 99%
“…Mechanistically, HPV inhibits basal and proinflammatory-induced host defense peptide expression by subverting the NF-κB and Wnt/β-catenin signaling cascades, thus leading to a significant reduction in the Lactobacillus species that rely on amino acid sources, which further promotes an imbalance in vaginal flora. In turn, oxidative stress resulting from BV infiltration promotes the progression of preneoplastic lesions ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another drug, lacidophilin vaginal capsule is a living bacterium preparation based on lactic acid bacteria (LAB), which can not only improve vaginal microecological flora and abnormalities of acid-base balance but also has a reactivation effect on vaginal immune defense [ 10 ]. It is worth mentioning that HPV infection will lead to the imbalance of vaginal microecology, disrupting the checks, and balances between LAB and other microorganisms [ 11 ]. Given the current lack of research on the application of lacidophilin vaginal capsules plus rh-IFN- α 2b in treating HPV-infected patients, we conduct relevant research in the hope of providing novel insights into the treatment of patients with HPV infection.…”
Section: Introductionmentioning
confidence: 99%